Comparative Study of MiroCam MC2000 and PillCam SB3 in Detecting Small Bowel Bleeding: A Multicenter Prospective Randomized Crossover Study - Ji Eun Kim; Eun Ran Kim; Jae Jun Park; Kyeong Ok Kim; Yehyun Park; Young Joo Yang; Hyun Joo Jang (Gut and Liver)
Background/Aims : The MiroCam MC2000 (MC2000) is a double-tip capsule with a camera on each side. It is designed to provide more extensive visualization of the small bowel mucosa, potentially reducing the chance of missing lesions. This study aimed to compare the detection rates for lesions in the ampulla of Vater (AoV) and the small bowel of the MC2000 and the PillCam SB3 (SB3) for patients with suspected small bowel bleeding. Methods : This prospective, multicenter, randomized crossover trial compared the lesion detection capabilities of the MC2000 and SB3 capsules, ingested one hour apart by patients with suspected small bowel bleeding. The primary outcome was the detection of lesions in the AoV, while the secondary outcome was the assessment of the detection of P1 and P2 lesions, known underlying causes of small bowel bleeding. Results : There was no significant difference in AoV lesion detection rates between the devices. However, MC2000 demonstrated significantly greater detection of red spots in patients with visible bleeding (p=0.018) and tended to detect a greater number of small bowel lesions, including P2 lesions. Minor complications included device stasis, with fewer incidents with the MC2000 than with the SB3, and one instance of small bowel retention due to ulcers. Conclusions : The MC2000’s dual-camera system appears to enhance the detection of small bowel lesions over the SB3, especially for more important lesions. These findings suggest that the MC2000 may offer superior diagnostic capabilities for patients with suspected small bowel bleeding, potentially leading to better clinical outcomes (this trial registered KCT0005591).